Test charge driven response of a dusty plasma with polarization force - Ali, S.; Masood, W.; Singh, K.; Jahangir, R. (Frontiers in Astronomy and Space Sciences, 2022)
By using the framework of a kinetic model, the test charge driven response of the dusty plasma is evaluated in the presence of polarization force. The plasma containing electrons, singly ionized positive ions and highly charged dust particulates is known as a dusty plasma, which can be perturbed by the test particle of charge q_{T} moving with velocity v_{T} along the z-axis. The polarization force purely comes from the high charging state of micron sized dust particles, causing a deformation of shielding length due to density gradient and modifies the collective motion and particulates' acceleration. The application of Fourier transformation technique to the set of dynamical equations may result in the shielded potential for a test charge with modified dielectric constant. Several possibilities are explored to evaluate the shielded potentials by imposing different conditions on the test charge speed in comparison with the thermal speeds of plasma species. It is found that the profiles of the wakefield (WF), Debye-Hückel (DH), and farfield (FF) potentials are strongly modified by the polarization force coefficient and dust concentration. The present findings are useful for the formation of dust crystallization and dust coagulation in the laboratory plasmas, where micron-sized charged dust particles of high charging state exist.